Kepuasan Pasien Terhadap Pelayanan Informasi Obat Pada Peresepan Antibiotik di Klinik Pratama Masyitoh, Kudus - Ria Etikasari; Lestaria, Diana Tri; Ruhmana, Faizzatur; Kurniawan, Galih (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Provision of Drug Information (PIO) was place for health facilities to optimize clinical pharmacy services in order to increase patient satisfaction.Objective: This study aims was to determine the relationship between PIO and patient satisfaction who received antibiotic prescriptions Method: Data was taken from outpatients and inpatients who do medical examinations from March to April 2024 at the Masyitoh Clinic, Kudus. A questionnaire was used to determine the completeness of PIO implementation and measure patient satisfaction. The results were analyzed using the chi-square statistical test to determine the relationship between the two variables. Results : 113 patients met the inclusion criteria and were willing to become respondents by filling out informed consent as well as the PIO questionnaire and patient satisfaction questionnaire. The age of the majority of patients was 18 – 30 years and 31 – 50 years (41.6%) with female gender (60.2%) and junior high school education (27.4%). The most widely used antibiotic was amoxicillin (51.3%). The majority of patients (69%) stated that PIO was complete and some (52.2%) patients stated that they were satisfied. The statistical test results obtained p value of 0.000. Conclusion: There is a relationship between PIO and patient satisfaction who receive antibiotic prescriptions in outpatient and inpatient settings.